2013
DOI: 10.1111/bph.12341
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline inhibits the transport of PAT1 substrates in vivo and in vitro

Abstract: Sertraline is an apparent non-competitive inhibitor of hPAT1-mediated transport in vitro. This inhibitory effect of sertraline is not specific to hPAT1 as substrate transport via hPepT1 and hSGLT1 was also reduced in the presence of sertraline. In vivo, sertraline reduced the amount of gaboxadol absorbed, suggesting that the inhibitory effect of sertraline on PAT1 occurs both in vitro and in vivo. Hence, sertraline could alter the bioavailability of drugs absorbed via PAT1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…To our knowledge, E2 and E-E2 are the most potent PAT1 inhibitors reported in the literature with affinities approximately 3e20 times higher than sertraline. 26 Moreover, the effect of E2 appeared within 5 min and could be rapidly washed out over a 15 min period, which suggested a direct and non-genomic interaction. In other shortterm experiments, E2 has been shown to inhibit transport via other membrane transport proteins: In striatal synaptosomes from ovariectomized Sprague Dawley rats, E2 decreased dopamine uptake in a competitive manner with an IC 50 value of 7.2 ± 0.6 mM, 36 E2 inhibited L-type Ca 2þ channels in A7r5 cells with an IC 50 value of 14.24 ± 0.05 mM, 37 and non-competitively inhibited mouse 5-HT 3 receptors with an IC 50 value of 33.2 mM.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To our knowledge, E2 and E-E2 are the most potent PAT1 inhibitors reported in the literature with affinities approximately 3e20 times higher than sertraline. 26 Moreover, the effect of E2 appeared within 5 min and could be rapidly washed out over a 15 min period, which suggested a direct and non-genomic interaction. In other shortterm experiments, E2 has been shown to inhibit transport via other membrane transport proteins: In striatal synaptosomes from ovariectomized Sprague Dawley rats, E2 decreased dopamine uptake in a competitive manner with an IC 50 value of 7.2 ± 0.6 mM, 36 E2 inhibited L-type Ca 2þ channels in A7r5 cells with an IC 50 value of 14.24 ± 0.05 mM, 37 and non-competitively inhibited mouse 5-HT 3 receptors with an IC 50 value of 33.2 mM.…”
Section: Discussionmentioning
confidence: 95%
“…22 Generally, one substrate may competitively inhibit the transport of another substrate, but a number of inhibitors for PAT1 have also been identified such as serotonin, L-tryptophan and 5-hydroxy-tryptophan (IC 50 of 5.9, 4.7 and 0.9 mM), 24 dipeptides such as Gly-Tyr, Gly-Pro, and Gly-Phe (IC 50 of approx. 30e50 mM), 25 and the anti-depressant sertraline (IC 50 of 177e241 mM), 26 opening the possibility of both food components and drug substances having the potential to alter PAT1mediated (victim) bioavailability. In oocytes injected with PAT1 cRNA it has been proposed that 17-a-estradiol and 17-b-estradiol decrease glycine induced inward currents at concentrations of 100 mM.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, tryptophan derivatives such as serotonin and 5-hydroxy-L-tryptohpan are non-transported competitive inhibitors of SLC36A1 [ 57 ]. Furthermore, a selective serotonin reuptake inhibitor, sertraline, inhibits SLC36A1 activity [ 58 ]. In addition, the SLC36A1 mRNA level is increased in the jejunum of high fat diet-fed mice [ 59 ], and the transcriptional activity of SLC36A1 is up-regulated by insulin in skeletal muscle cells [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the amino acid inhibitors had a similar affinity to the normal substrates, the dipeptides had a much lower affinity. Later, high-affinity inhibitors such as the anti-depressant sertraline (IC 50 of 177–241 µM, Figure 6 ) [ 266 ] and 17-α-estradiol and 17-β-estradiol (E2, Figure 6 ) were identified [ 267 ]. Shan et al suggested that estradiol binds to PAT1 and thereby changes the conformation of the PAT1 protein from an open to a closed state, thereby decreasing transport activity [ 267 ].…”
Section: Proton-coupled Amino Acid Transporter 1 (Pat1)mentioning
confidence: 99%